The Significance of Death-scene Investigation in Determining Cause and Circumstances of Medicolegal Death - Crișan, Corina (Journal of Legal Studies, 2019)
The article presents two cases of the Arad Medico-Legal Department illustrating just a part of the role of the forensic pathologist at the death scene but there are sufficient to fully justify the importance of this investigation as no example can comprise the complexity of problems and the particularity of each case, nor a statistic can be made. Both cases were found dead at home and forensically autopsied, but the two of them were distinct in terms of forensic pathologist's request death scene participation. In the first case, the autopsy did not find traumatic lesions, but revealed that the death was due to massive hemoptysis caused by cavernous tuberculosis with subsequent exsanguination, microscopically confirmed. The death was nonviolent. In the second case, the autopsy revealed findings of mechanical asphyxia due to neck compression, both macroscopically and microscopically. The death was violent. In both cases the forensic expert participation is required at the death-scene. In the first case it allowed the correct interpretation of the traces of blood found on site, and in the second case, an onsite research would have properly helped for restoring the death‟s occurrence. The scene investigation and autopsy provide, together, the basis for an accurate determination of cause and circumstances of death.